Strategi Pengembangan Obyek Wisata Goa Tengkorak Batu Kajang sebagai Atraksi Pariwisata - Rustika, Ranti (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2020)
Â This study aims to identify internal and external factors that support and hold up the development of attractions in Goa Tengkorak. This Study also aims to describe a strategy for tourism development Goa Tengkorak by using SWOT analysis. The method used in this study was descriptive qualitative method.The results showed thatthe supporting factor in developing Goa Tengkorak is the human skull in the cavewhich is a unique attraction and this location near another tourist attraction have chance to be sustainable tourism. On the other side, the inhibitors factor in developing Goa Tengkorak is there is no expert team of who conduct regular maintenance of the skulls in the cave and the weakness of regulation to managing Goa Tengkorak. Referring to these factors, a suitable development strategy for the Goa Tengkorak is to re-organize the